RELEVANSI PROGRESIVISME DENGAN PEMBELAJARAN ABAD 21 DALAM MENINGKATKAN KUALITAS PENDIDIKAN MENUJU INDONESIA EMAS 2045: Relevansi Prinsip Progresivisme dengan Kompetensi Abad 21, Peran Guru Sebagai Fasilitator dan Siswa Sebagai Subjek Aktif, Keterkaitan Progresivisme dengan Demokrasi Pendidikan, Relevansi Progresivisme dalam Menghadapi Bonus Demografi, Konstribusi Progresivisme Terhadap Visi Indonesia Emas 2045 - mardewi, mardewi; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the relevance of progressivism philosophy to 21st-century learning in improving the quality of education toward realizing Indonesia Emas 2045. The research employs a qualitative approach using library research focused on conceptual analysis of national and international scholarly articles published between 2018 and 2025. Content analysis and a hermeneutic approach were used to interpret experts’ perspectives on the interrelation between progressivism principles, 21st-century competencies, and national education policy. The findings reveal that progressivism is highly relevant to the development of student-centered learning, experiential learning, and the enhancement of critical thinking, creativity, collaboration, and communication skills (4C). John Dewey’s principle of learning by doing effectively supports the mastery of 21st-century competencies through contextual and democratic learning experiences. In the Indonesian context, progressivism aligns with the spirit of the Merdeka Curriculum and the Pancasila Student Profile, which emphasize independence, collaboration, and character formation. The application of progressive values is believed to strengthen the development of adaptive, innovative, and globally competitive human resources, making education the fundamental pillar in achieving the vision of Indonesia Emas 2045.